Manajemen Konflik Berdasarkan Nilai-Nilai Islam di Lingkungan Pendidikan Multikultural - Ma'rufah, Afni (EDUKASIA Jurnal Pendidikan dan Pembelajaran, 2023)
The urgency of conflict management in a multicultural educational environment and the diverse backgrounds of students in Islamic schools is increasing. Islamic values have great potential in offering effective and peaceful conflict management solutions. This study aims to identify relevant Islamic values and analyze their application in conflict management in a multicultural educational environment. This study uses a literature review method by researching various literature related to Islamic values, conflict management, and multicultural education. Data is obtained from various sources such as books, journals, articles, and other related documents. Data analysis was carried out thematically to identify the main themes regarding Islamic values in conflict management and conflict management models or frameworks based on Islamic values. The results of the study are expected to show that values such as justice, patience, tolerance, and peace are important components that can be applied in conflict management in a multicultural educational environment. Challenges in implementing these values include limitations in understanding and training for educators and cultural resistance. These findings are also expected to make theoretical and practical contributions to Islamic education management and provide guidance for education practitioners to manage conflicts more effectively and inclusively.